MOTIVATION OF THE GOVERNMENT OF SINGAPORE INVESTMENT CORPORATION (GIC) PTE. LTD TO INVEST IN INDONESIAN 2016 - Claudia, Chici (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research describe Motivation of the Government of Singapore Investment Corporation (GIC) Invest in Indonesian 2016. Indonesia is a country whose economy is developing well in the Southeast Asia region. Many countries want to invest in Indonesia, one of them is Singapore, Singapore has Government of Singapore Investment Corporation (GIC) Pte Ltd which is a government-owned company assigned to manage Singapore's sovereign wealth funds.The study was prepared using the international cooperation by KJ.Holsti and the Foreign Direct Investment (FDI) theory, the neoliberalisme perspective, and Multinational Coorperations (MNCs) analysis. This research also used descriptive analysis with qualitative approach. Data collection techniques used library research . The results of this study indicate the motivation of the Government of Singapore Investment Corporation Invests in Indonesia in 2016 because Indonesia has economic opportunity, Indonesia is a potential market, Indonesia is a consumptive country, and Indonesia has relatively stable politics and security.Keywords: Motivation, Investment, Government of Singapore Corporatin (GIC) Pte Ltd, Indonesia, Singapore